Gzmk+ CD8 T cells in inflammatory diseases - Xin, Cui; Liu, Peiyun; Zhan, Qianqian; Cao, Wenqiang (Frontiers in Immunology, 2025)
T cells are integral to the immune response, with distinct subsets exhibiting specialized functions, a phenomenon well-characterized in helper CD4+ T cells. Recent advancements in single-cell RNA sequencing (scRNA-seq) have facilitated the identification of numerous novel CD8 T cell subsets, each characterized by unique functional properties. As cytotoxic T lymphocytes, the primary focus has been on the cytotoxic capabilities and antigen specificity of these subsets. A recently identified subset, Granzyme k (Gzmk)+ CD8 T cells, has been closely associated with inflammatory diseases, independent of their cytotoxic function. Unlike other granzymes, granzyme K predominantly induces proinflammatory responses in tissues or cells rather than mediating cytotoxicity. This review synthesizes current evidence regarding the regulation, functional roles, and underlying mechanisms of Gzmk+ CD8 T cells in inflammatory conditions. Elucidating these processes may reveal potential therapeutic targets for treating inflammatory diseases.